THE ROLE OF HYDRONYMS IN THE MANIFESTATION OF THE SYMBOLISM OF POETIC TEXTS (Revista Inclusiones, 2019)
The article is devoted to the study of water symbolism in the poetic texts of the Silver age of the Russian poetry. The question of what is the semantics interested philosophers, linguists, psychologists since ancient times. The points of view of scientists on the theory of semantics and archetype are different and diverse. Most scientists agree that the archetype is an archaic phenomenon, so it appears in myths and folklore. Attention is paid to the distinction between linguistic and artistic metaphors-archetypes. The article studies the question of the semantics of water space in the poetic text. Water metaphors in lyrical texts of the Silver age literature, interaction and connection of water images with ancient texts are analyzed. Traditional rhymes (вода – беда, море – горе, etc.) that incorporate structural and semantic options have become the point of the research.